(untitled) (Research, Society and Development, 2021)
Gorlin Goltz syndrome is a rare and autosomal dominant genetic condition that affects several organs and systems, and basal cell carcinomas, odontogenic keratocysts, bone and neurological structural abnormalities can be identified. The objective of this work is to elucidate the main criteria for the correct diagnosis and to expose a surgical clinical case. Male patient, 14 years old, leucoderma, presented with a complaint of severe headache and visual impairment. The physical examination revealed an increase in chest diameter, low implantation of the ears, hypertelorism and asymmetry of the face on the left side. The face and skull tomography revealed calcification of the falx cerebri and multiple lesions in the gnathic bones. On chest tomography, rib bifida and kyphoscoliosis were observed. The patient was evaluated by the ophthalmology team, who concluded that the visual deficit was due to the compression of the optic nerve by a large lesion in the maxilla. It was then planned and performed the decompression surgery of the maxillary lesion and enucleation of the mandibular lesions, which, through histopathology, confirmed that it was multiple keratocysts, thus defining the diagnosis of Gorlin Goltz syndrome through the identification of several criteria relevant according to Kimonis et al., 1997. In the post-surgical period, the patient had a complete remission of complaints of headache and visual impairment. Gorlin Goltz syndrome can evolve rapidly with harmful consequences for different organs, even in youngs patients, which reinforces the importance of early diagnosis and a multidisciplinary approach.